Autorrepresentação de adolescentes porto-alegrenses no Instagram - Fantoni, Andressa (2017)
This work aims to understand how teenagers of Porto Alegre/RS represent themselves on Instagram and how the features of the social network – that is, the instantaneity in capturing and sharing images and the aesthetic orientation of the application – influence on the communication of these subjects. In order to contextualize the research, it starts from the presentation of a theoretical contribution on youth, youth cyberculture practices and selfpresentation. Next, it discusses the mobile internet and mobile access devices, as well as the concept of mobile social networks. The qualitative method is used to collect data about young Instagram users, the semi-structured interview being the main one among the techniques employed. Data found on field show that adolescents elaborate images of themselves with some caution, and the instantaneous condition of Instagram is neglected by these young people.